Differential Spatiotemporal Expression of Type I and Type II Cadherins Associated With the Segmentation of the Central Nervous System and Formation of Brain Nuclei in the Developing Mouse - Polanco, Julie; Reyes-Vigil, Fredy; Weisberg, Sarah D.; Dhimitruka, Ilirian; Brusés, Juan L. (Frontiers in Molecular Neuroscience, 2021)
Type I and type II classical cadherins comprise a family of cell adhesion molecules that regulate cell sorting and tissue separation by forming specific homo and heterophilic bonds. Factors that affect cadherin-mediated cell-cell adhesion include cadherin binding affinity and expression level. This study examines the expression pattern of type I cadherins (Cdh1, Cdh2, Cdh3, and Cdh4), type II cadherins (Cdh6, Cdh7, Cdh8, Cdh9, Cdh10, Cdh11, Cdh12, Cdh18, Cdh20, and Cdh24), and the atypical cadherin 13 (Cdh13) during distinct morphogenetic events in the developing mouse central nervous system from embryonic day 11.5 to postnatal day 56. Cadherin mRNA expression levels obtained from in situ hybridization experiments carried out at the Allen Institute for Brain Science (https://alleninstitute.org/) were retrieved from the Allen Developing Mouse Brain Atlas. Cdh2 is the most abundantly expressed type I cadherin throughout development, while Cdh1, Cdh3, and Cdh4 are expressed at low levels. Type II cadherins show a dynamic pattern of expression that varies between neuroanatomical structures and developmental ages. Atypical Cdh13 expression pattern correlates with Cdh2 in abundancy and localization. Analyses of cadherin-mediated relative adhesion estimated from their expression level and binding affinity show substantial differences in adhesive properties between regions of the neural tube associated with the segmentation along the anterior–posterior axis. Differences in relative adhesion were also observed between brain nuclei in the developing subpallium (basal ganglia), suggesting that differential cell adhesion contributes to the segregation of neuronal pools. In the adult cerebral cortex, type II cadherins Cdh6, Cdh8, Cdh10, and Cdh12 are abundant in intermediate layers, while Cdh11 shows a gradated expression from the deeper layer 6 to the superficial layer 1, and Cdh9, Cdh18, and Cdh24 are more abundant in the deeper layers. Person’s correlation analyses of cadherins mRNA expression patterns between areas and layers of the cerebral cortex and the nuclei of the subpallium show significant correlations between certain cortical areas and the basal ganglia. The study shows that differential cadherin expression and cadherin-mediated adhesion are associated with a wide range of morphogenetic events in the developing central nervous system including the organization of neurons into layers, the segregation of neurons into nuclei, and the formation of neuronal circuits.